Analisis Kualitas Pengelolaan Bus Tayo Dalam Mewujudkan Kota Tangerang Sebagai Smart City - Eko Prasetyo; Refly Badar; Isma Nuzullani (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
Tangerang City Government has implemented a smart city policy, with public transportation via Bus Tayo being one of its programs. The difficulties encountered in managing Bus Tayo include a lack of integration with other modes of transportation, a lack of reliability of facilities on board, inaccurate schedules, and inflexible payment systems. This study aims to analyze the community satisfaction index towards Bus Tayo services and the quality of bus management by the operator. This study employs a mixed method (quantitative and qualitative). The quantitative data came from passenger perception surveys, and the qualitative data came from interviews, observations, and document studies, with key informants being PT. Tangerang Nusantara Global officials. Result show that the community satisfaction index on Bus Tayo services is 68.55 with a good predictor. All performance targets, namely environmental sustainability, safety, physical and social accessibility, reliability and consistency, integration of micromobility, and integration of information and communication technology, have not been met in terms of Bus Tayo management quality. As a result, increasing the number of human resources, improving the service culture, improving the quality of bus infrastructure and facilities, and implementing a flexible multi-payment system are all necessary.